Предмет: Математика,
автор: nastiatygunova
Упростить выражение: -5х+6х-(х-6)+(-3х+7).
Ответы
Автор ответа:
2
Ответ:
Удачи
Пошаговое объяснение:
-5х+6х-(х-6)+(-3х+7)= -5х+6х-х+6+(-3х)+7= -5х+6х-х-3х+6+7= -3х+13
Автор ответа:
0
Ответ:
-3х + 13
Пошаговое объяснение:
-5х + 6х - (х - 6) + (-3х + 7) =
-5х + 6х - х + 6 - 3х + 7 =
(-5 + 6 - 1 - 3) * х + (6 + 7) =
-3 * х + 13 = -3х + 13
Похожие вопросы
Предмет: Русский язык,
автор: otash07071
Предмет: Русский язык,
автор: anastasiyamyalik
Предмет: Русский язык,
автор: 12шох12
Предмет: Физика,
автор: Помощник5единорожек
Предмет: Русский язык,
автор: blackhood22